2006
DOI: 10.1597/04-114r.1
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Prominent Premaxilla in Bilateral Cleft Lip and Palate

Abstract: With appropriate patient selection, bilateral alveolar bone grafting with premaxillary repositioning is a safe procedure and can produce good aesthetic and functional results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 10 publications
0
23
0
1
Order By: Relevance
“…In their article, Aburezq et al [ 22 ] describe four patients who were treated with an osteotomy of the premaxilla combined with secondary alveolar bone grafting. There was no loss of the premaxilla, and good consolidation was seen in three patients.…”
Section: Resultsmentioning
confidence: 99%
“…In their article, Aburezq et al [ 22 ] describe four patients who were treated with an osteotomy of the premaxilla combined with secondary alveolar bone grafting. There was no loss of the premaxilla, and good consolidation was seen in three patients.…”
Section: Resultsmentioning
confidence: 99%
“…Osteotomy of PM at secondary alveolar bone grafting is considered ideal [6]. Commonly encountered complications in these types of cases where the loss of alveolar bone graft and mobility of PM due to fibrous union or non-union.…”
Section: Discussionmentioning
confidence: 99%
“…It also requires the second stage for removal of an arch bar and maintaining of oral hygiene is difficult so it is our least preferred method of fixation. Alexander et al in 1990 reported a prefabricated appliance aid in stabilization, using that idea we fabricated two different devices, which had been used in second and fifth cases [6]. But challenges faced during surgery were poor control over the osteotomized PM and three-dimensionally inadequate stability of bodily movement of the osteotomized PM.…”
Section: Discussionmentioning
confidence: 99%
“…Some unilateral alveolar clefts will also require premaxilla osteotomy and repositioning where cleft lip repair had been neglected or overly delayed. Some authors advocated the amputation of the premaxilla [21], while others prefer to reposition it [22]. Where possible, it is preferable to pre-serve the native bone of the premaxillary segment so that amputation should be the last resort.…”
Section: Discussionmentioning
confidence: 99%